Self-Efficacy for Adoption and Maintenance of Exercise Among Fibromyalgia Patients: A Pilot Study. Issue 4 (July 2020) - Scioli-Salter, Erica R.; Smith, Brian N.; McSheffrey, Savannah; Bair, Matthew J.; Sillice, Marie A.; Driscoll, Mary; Higgins, Diana M.; Allsup, Kelly; Amalathas, Aneline; Gerber, Megan R.
Objective . While multimodal treatment approaches for fibromyalgia (FM), incorporating exercise, have been found most effective, information about factors associated with exercise adoption and maintenance is lacking. Design, Setting, and Methods . Women veterans with FM (N = 19) completed an anonymous Internet survey measuring FM impact (FI), adoption of exercise behavior, and self-efficacy for exercise. Using classifications of behavior specified by the transtheoretical model, the self-efficacy of participants classified in the action or maintenance (AM) stages was compared with those in earlier stages (precontemplation through preparation) of exercise readiness. Multivariate analysis of variance analyses examined differences in FI domains by stage of change. Analysis of covariance examined whether exercise self-efficacy differed by stage of change while controlling for FI. Results . Higher levels of self-efficacy were detected among participants in the AM stages. Participants in the AM stages also reported higher levels of FI symptoms. After controlling for FI, self-efficacy did not differ significantly between the 2 groups; however the effect size was large (η 2 = .11). Conclusions . Findings of this pilot study suggest a role for self-efficacy in exercise adoption and maintenance, even in the setting of higher FM symptoms. Replication of this study with a larger sample size is warranted.